Hong Kong a family portrait [videorecording] - Kane, Dennis B.; Skinner, Thomas; National Geographic Society; WQED (Television station : Pittsburg, Pa.). (Washington, D.C. The Society, 1978)
Focuses on Hong Kong by following the daily experiences of a resident Chinese family.
VHS.
Narrated by Burgeos Meredith ; Photography by Robert Young ; edited by Barry Nye.
Keywords: Family -- Hong Kong; Family life. -- Hong Kong; Hong Kong -- Social life and customs